(untitled) (Applied Biological Research, 2023)
The present study was aimed to characterize the Trichoderma species prevailing in the major pulse growing areas of India. The Trichoderma isolates (54) were collected from the rhizospheric soils of chickpea, pigeonpea and rice-pulse cropping system in Madhya Pradesh, Uttar Pradesh and Maharashtra states of India. The isolates were characterized using their culturemorphological and molecular characteristics. Compact mycelial growth of Trichoderma spp. was seen in PDA medium, less dense growth in malt extract agar and powdery growth in oatmeal agar. Colony colour in media was generally green to dark green and occasionally yellowish green to dark green with white tinge; and the pigmentation in the reverse side varied from white, yellowish or faint yellow. Phialides were ampulliform to sub-globose or lageniform divergent or crowded whorls of 2-5, the middle of phialides were markedly swollen, conidia were sub globose to ovoid, the conidiophores highly branched having intercalary or terminal chlamydospores of sub-globose to ellipsoid or pyriform shape. Based on PCR amplification of ITS region sequences 44 isolates were characterized at molecular level. The partial ITS sequences were analyzed using MegaBLAST with NCBI GenBank database to confirm their identity. The study revealed the presence of 5 species of Trichoderma viz., viride, T. asperelloides, T. koningiopsis, T. asperellum and T. harzianum.